2013
DOI: 10.1227/01.neu.0000430320.39870.f7
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Transforaminal Lumbar Interbody Fusion With 1 or 2 Cages by Finite-Element Analysis

Abstract: Single-cage TLIF approximates biomechanical stability and increases the stress of the bone graft. The use of a single cage may simplify the standard TLIF procedure, shorten operative times, decrease cost, and provide satisfactory clinical outcomes. Thus, single-cage TLIF is a useful alternative to traditional 2-cage TLIF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 21 publications
3
46
1
Order By: Relevance
“…Compared with previous PLIF FE models [16, 17, 24], the current PLIF FE model focused on the important role of posterior complex. Biomechanically, posterior complex acts as the posterior tension band in flexion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with previous PLIF FE models [16, 17, 24], the current PLIF FE model focused on the important role of posterior complex. Biomechanically, posterior complex acts as the posterior tension band in flexion.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PLIF has been reported to be more rigid than posterolateral fusion [28, 29], and hence patients who undergo are likely to experience a higher incidence of ASD than those who underwent posterolateral fusion [30]. However, most previous PLIF FE analyses have neglected the importance of posterior complex and focused on the altered biomechanical behavior in the fused lumbar spine with spinal fixators and cages [16, 17, 24, 28, 29]. Therefore, our FE model found that the preserved posterior complex led to less ROM, IDP and ligament forces on the proximal adjacent segment in flexion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, ABAQUS software (version 2016, Simulia Inc., USA) was used to set the properties of the lumbar spine components. The material properties were described in the previous literature as specified in Table 1 [16][17][18].…”
Section: Methodsmentioning
confidence: 99%
“…In our institution, the PLIF group used a paired cage and the TLIF group used a single cage. We used a single cage as successful fusion can be achieved with a single cage alone in TLIF [16]. In this study, l4 of 40 cages were located in the contralateral position, nine cages in the middle position, and 17 in the ipsilateral position in the TLIF group.…”
Section: Discussionmentioning
confidence: 99%